Acquired Abnormalities of Plasma Von Willebrand Factor Related Parameters and ADAMTS13 Autoantibodies in Aggressive Haematological Malignancies. - Dzarr AA; W Zaidah A; Azlan H (Journal of Hematology and Oncology Research, 2015)
Background Abnormalities of plasma von Willebrand Factor (vWF) system has been described in solid tumors but more information is required to understand the pathophysiological process in haematological malignancies. Objectives This study was carried out to investigate the changes in vWF-related parameters including ADAMTS13 protein level in aggressive haematological malignancies and to identify the prevalence of anti-ADAMTS13 antibody as well as its correlations with vWF-related parameters. Patients/Methods Patient newly diagnosed or having relapse acute leukaemias or aggresive non-Hodgkin lymphomas were recruited into this study. Exclusion criterias include; pregnancy, patient already commenced chemotherapy, sepsis or has background congenital bleeding disorders. Blood specimen was subjected to; blood counts, ADAMTS13 protein, ADAMTS13 antibody detection, vWF:Ag, vWF activity, factor VIII level (FVIII) and vWF: CBA (collagen binding assays) Results and Conclusion A total of 60 subjects with median age at 42.5 (IQR: 23.25-57.5) were included. There were 34(56.7%) lymphomas and 26(43%) acute leukaemias. FVIII, vWF:Ag, wVF activity and vWF:CBA level were elevated whereas ADAMTS13 protein was reduced in majority of patients. Those with lymphomas showed significantly higher levels of FVIII, vWF:Ag, vWF:activity and vWF:CBA compared to the leukaemias. 38(63.3%) of patients showed presence of ADAMTS 13 autoantibody. There was however no correlation between ADAMTS13 protein and vWF-related parameters or with ADAMTS13 autoantibodies. There was a high prevalence of ADAMTS 13 autoantibodies in this cohort despite the absence of thrombotic thrombocytopenic purpura (TTP). The more pronounced changes in vWF-related parameters among aggressive lymphomas compared to acute leukaemias are in tandem with the marginally higher rates of venous thromboembolism in the former.
Keywords: ADAMTS13 antibodies